2018
DOI: 10.1038/s41598-018-33168-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ylHog1 MAPK kinase on Yarrowia lipolytica stress response and erythritol production

Abstract: Erythritol production is a unique response to hyperosmotic stress that is observed in a small group of yeasts, including Yarrowia lipolytica. This study investigated whether this unusual mechanism is regulated by the HOG pathway, well described in Saccharomyces cerevisiae. The gene YALI0E25135g was identified as the Y. lipolytica homologue of HOG1 and was found to be phosphorylated in response to hyperosmotic shock. Deletion of the gene caused a significant decrease in resistance to hyperosmotic stress and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The Bioscreen C has been used to determine the growth curve of Y. lipolytica in recent years (Lazar et al, 2011; Dobrowolski et al, 2016; Mirończuk et al, 2016, 2017; Rzechonek et al, 2018). Under the culture condition we used for Bioscreen C analysis, relatively a small proportion of cells changed from typical yeast form to filamentous form (as examined using Cellometer), which was not significant enough to disrupt the turbidity readings.…”
Section: Resultsmentioning
confidence: 99%
“…The Bioscreen C has been used to determine the growth curve of Y. lipolytica in recent years (Lazar et al, 2011; Dobrowolski et al, 2016; Mirończuk et al, 2016, 2017; Rzechonek et al, 2018). Under the culture condition we used for Bioscreen C analysis, relatively a small proportion of cells changed from typical yeast form to filamentous form (as examined using Cellometer), which was not significant enough to disrupt the turbidity readings.…”
Section: Resultsmentioning
confidence: 99%
“…In response to osmotic stress, Y. lipolytica produces erythritol and arabitol [ 33 , 43 ]. Osmotic stress yields a significant increase in erythritol production during growing on glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…Relating this phenotype to expression analysis, UMAG_02357 (putative mitogen-activated protein kinase HOG1) expression was affected by nrg1 mutation. Some studies have related this gene function with cell wall adjustments related to osmotic stress adaptation and yeast-to-hyphae transition [ 68 ]. Moreover, from the promoter analysis, it was found that Rim101 and Nrg1 canonical binding sites are present on the 5’ DNA region of these open reading frames.…”
Section: Discussionmentioning
confidence: 99%